WHY SHOULD WE CHOOSE SHARIAH FINTECH OVER SHARIAH BANKS: AN INVESTMENT ANALYSIS - Bin-Armia, Muhammad Syauqi (Jihbiz: Global Journal of Islamic Banking and Finance, 2024)
The article investigated an analysis the preference between Shariah fintech and Shariah banks through an investment perspective. The rise of Islamic fintech represents a significant development in the financial landscape, offering a blend of Islamic finance principles with financial technology. This sector has seen rapid growth, expanding from a few companies in 2016 to over 200 by 2021. This making Shariah fintech not only promotes financial inclusion by reaching underserved populations but also supports the development of the MSMEs. Meanwhile, the Shariah banking industry facing a decline, particularly the investors’ preferences in the financial industry. Does this mean the Shaiah fintech successfully competes with traditional Shariah banks by offering greater flexibility, faster transactions, and lower costs, appealing particularly to younger, tech-savvy consumers? As an outcome, the research will be qualitatively examined utilising the library study approach and employing scientific research and publications as secondary data. The study concluded that Sharia fintech has proven global development with soaring market size. This significantly contributed to social impacts, direct investment, and reliability.